Does Religiosity Promote Property Rights and the Rule of Law? - Niclas Berggren; Christian Bjørnskov (Research Institute of Industrial Economics (IFN), 2012)
Social and cultural determinants of economic institutions and outcomes have come to the forefront of economic research. We introduce religiosity, measured as the share for which religion is important in daily life, to explain institutional quality in the form of property rights and the rule of law. Previous studies have only measured the impact of membership shares of different religions, with mixed results. We find, in a cross-country regression analysis comprising up to 112 countries, that religiosity is negatively related to our institutional outcome variables. This only holds in democracies (not autocracies), which suggests that religiosity affects the way institutions work through the political process. Individual religions are not related to our measure of institutional quality.
Keywords: K11; K42; Z12; 330; Religion; Religiosity; Rule of law; Property rights; Institutions; Religion; Rechtsstaat; Eigentumsrecht; Institutionalismus; Welt